Proteome analysis of human CD56neg NK cells reveals a homogeneous phenotype surprisingly similar to CD56dim NK cells. Issue 9 (1st August 2018) - Voigt, Jenny; Malone, David F.G.; Dias, Joana; Leeansyah, Edwin; Björkström, Niklas K.; Ljunggren, Hans‐Gustaf; Gröbe, Lothar; Klawonn, Frank; Heyner, Maxi; Sandberg, Johan K.; Jänsch, Lothar
Abstract: NK cells lacking CD56 (CD56 neg ) were first identified in chronic HIV‐1 infection. However, CD56 neg NK cells also exist in healthy individuals, albeit in significantly lower numbers. Here, we provide an extensive proteomic characterisation of human CD56 neg peripheral blood NK cells of healthy donors and compare them to their CD56 dim and CD56 bright counterparts. Unbiased large‐scale surface receptor profiling clustered CD56 neg cells as part of the main NK cell compartment and indicated an overall CD56 dim ‐like phenotype. Total proteome analyses of CD56 neg NK cells further confirmed their similarity with CD56 dim NK cells, and revealed a complete cytolytic inventory with high levels of perforin and granzyme H and M. In the present study, twelve proteins discriminated CD56 neg NK cells from CD56 dim NK cells with nine up‐regulated and three down‐regulated proteins in the CD56 neg NK cell population. Those proteins were functionally related to lytic granule composition and transport, interaction with the extracellular matrix, DNA transcription or repair, and proliferation. Corroborating these results, CD56 neg NK cells showed modest cytotoxicity, degranulation, and IFN‐ɣ secretion as compared to CD56 dim NK cells. In conclusion, CD56 neg NK cells constitute functionally competent cells sharing many features of bona fide CD56 dim NK cells in healthy individuals, but with some distinct characteristics. Abstract : CD56 negative NK cells are under debate in patients with chronic viral infection. Here, we have now defined their molecular phenotype in healthy individuals. Extensive proteome data revealed the closest relation of CD56 neg to CD56 dim NK cells and, in parallel, confirmed their functional distinctness in activation and lytic granule pathways.